Planning and Scheduling for Maritime Container Yards Supporting and Facilitating the Global Supply Network - Li, Wenkai; Wu, Yong.; Goh, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Maximizing reader insights into the challenges facing maritime supply chains and container port logistics service providers in Asia, this book highlights their innovative responses to these challenges through real-world case studies. With a focus on mathematical modeling, simulation and heuristics approaches, this book provides academics, engineers, container terminal operators, students in logistics and supply chain management with the latest approaches that can be used to address the planning and scheduling problem in large container terminal yards. This book can be used on a self-contained basis as teaching cases in an undergraduate or specialist class setting, or on techniques applied to maritime container operations for port operations.
Introduction -- Maritime Terminal Operational Problems -- Discrete Time Model and Algorithms for Container Yard Crane Scheduling -- A Continuous Time Model for Multiple Yard Crane Scheduling with Last Minute Job Arrivals -- Heuristic Approach -- Validation via Simulation.
Keywords: Engineering; Transportation; Production management; Engineering economics; Engineering economy; Building construction; Engineering; Offshore Engineering; Engineering Economics, Organization, Logistics, Marketing; Operations Management; Transportation; Electronic books